Determination of the dependence of competitive results on the procedure of sports selection among Greco-Roman wrestlers - Nagovitsyn, R.; Osipov, A.; Kapustin, A.; Anfilatova, O.; Senator, S. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
Introduction : the problems of sports selection and selection of prospective children in martial arts schools are quite relevant in the sports practice. It was revealed the use of various selection techniques in the practice of martial arts. There is no unified methodological system for selection in martial arts schools. The purpose of the study : to determine the dependence of the dynamics of sports results of elite athletes on the procedure of sports selection (for example, the Greco-Roman wrestling). Material and methods : elite Greco-Roman wrestlers (n = 114) took part in the research. Age of athletes: 25-45 years. Qualification: International masters of sport (n = 8), masters of sport (n = 49), candidates in masters of sport (n = 57). Athletes filled out a diagnostic card with data on the procedure of sports selection. It was indicated the dynamics of competitive results during the sports career. Indicators of performance and stability of athletes were calculated applying the mathematical statistics methods ( ). The reliability of the results was determined by Student's t-test. Results : Data analysis showed that a significant part of athletes did not pass the selection procedure (n = 23). Many athletes passed only a partial selection procedure (n = 39). Some athletes did not pass the selection procedure. These athletes are not inferior in terms of stability to athletes who passed the selection at the 1st and 2nd levels of competitive results. In subsequent competitions, these athletes demonstrated the reliable (P <0.05) decrease in indicators of stability in comparison with other athletes. It was revealed a significant (P <0.05) advantage in indicators of stability among athletes who passed a partial selection procedure at the 4th level of competitive results. Conclusions : It was found the dependence of stability indicators at high levels of competitive results on the selection procedure of athletes. The athletes who passed the selection procedure demonstrate higher stability at high levels of competitive results. It was revealed a formal attitude to the selection procedure in some coaches and specialists. The trainers do not pay due attention to the indicators of maintaining body balance and coordination abilities during the selection of candidates. It has been revealed that the motor tests applied in the selection procedure do not allow an objective assessment of the potential of athletes' competitive achievements.